Punctuality in the Commencement of Judicial Proceedings: A Critical Analysis of its Implementation and Consequences Under the General Organic Code of Procedures - Sailema Armijo Juan Giovani; Miranda Chávez Luís Rodrigo; Soxo Andachi Jorge Washington; Andrade Santamaría Danil Rafael (Kurdish Studies, 2024)
This scientific article addresses the issue of punctuality in the commencement of judicial proceedings in Ecuador, specifically after the transition to an oral justice system. The importance of orality in the administration of justice is emphasized, promoting principles such as immediacy, concentration, and contradiction to achieve greater transparency, efficiency, and participation of the parties in the processes. It is emphasized that punctuality in the commencement of judicial proceedings has been a challenge following the abolition of the old practice of the "judicial hour." This custom allowed unjustified delays, which affected the principles of effectiveness and expeditiousness that were intended to be promoted by the oral system. The General Organic Code of Procedures in 2015 represented a significant step forward in addressing this issue by eliminating the "judicial hour" and establishing rules for the punctual commencement of judicial proceedings. This reform has contributed to improving punctuality, although challenges persist, such as strengthening the culture of punctuality among legal professionals and justice operators to ensure punctuality in practice. The article highlights that the debate on punctuality in the judicial system is relevant to maintaining effectiveness and trust in the system, and it emphasizes the importance of adhering to the established timelines for judicial proceedings to ensure legal certainty.